FINANCIAL LITERACY AND INCLUSION : STUDY BEHAVIORAL ADAPTATION OF FINANCIAL MANAGEMENT IN THE NEW NORMAL ERA OF THE HOPE FAMILY PROGRAM AT THE SOCIAL SERVICE OF MALANG CITY - Indri Kharisma; Ardi Bachtiar; Ananda Hadistia (SEAN Institute, 2023)
The ongoing Covid-19 pandemic has caused various problems, including a drastic decline in the financial sector. This situation has also affected various business sectors, including the government sector. The government sector is expected to provide financial management education to the recipients of the Family Hope Program (Program Keluarga Harapan or PKH) in the Department of Social Affairs of Malang City. Therefore, the government sector is required to be cautious in the preparation of financial reports for the social funds allocated to the PKH beneficiaries in the Department of Social Affairs of Malang City. This study aims to examine the influence of financial literacy and financial inclusion on financial management behavior in the new normal era at the Department of Social Affairs of Malang City. This is a qualitative research study that utilizes questionnaire as the data collection technique. The objectives of this study are (1) to identify and describe the attitudes and responses of PKH beneficiaries regarding financial literacy, (2) to identify and describe the attitudes and responses of PKH beneficiaries regarding financial inclusion, and (3) to determine and describe the extent of the implications of financial management in the new normal era. The qualitative method used in this research, as described by Miles, Huberman, and Saldana (2014:14), consists of three concurrent activities, namely data reduction, data display, and conclusion drawing or verification. Data were collected through interviews, observations, and documentation. Data analysis was conducted using four stages, including data collection, data reduction, data display, and conclusion drawing.